(untitled) (Journal of Environmental Science and Natural Resources, 2013)
The paper deals with the investigation of the fatty oil of carom seed (Trachyspermum ammi) for its physicochemical characteristics and fatty acid composition. Oil from carom seed collected from local market was extracted with n-hexane in a glass Soxhlet apparatus. Extracted oil was dark green, burning taste, spicy in odour and soluble in n-hexane, chloroform, pet. ether and benzene. Its chemical characteristic such as acid value (6.69), Iodine value (79.39), Peroxide value (457.11), Saponification value (184.32), Unsaponified matter (9.11), Free fatty acid value as petroselinic acid (48.1) were determined by conventional method. The composition of fatty oil was determined by Gas Liquid Chromatography (GLC). From GLC analysis the main constituents of fatty oil such as Petroselinic acid (89.35%), Oleic acid (5.86%), Linoleic acid (4.79%) were determined. For the better evaluation of these spices, it is necessary to know their complete chemical composition. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14571 J. Environ. Sci. & Natural Resources, 5(2): 15-21 2012